Criminological characteristics of persons committing domestic violence - Kalybaeva Алия (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article examines the content of the criminological characteristics of offenders who commit domestic violence. This question is relevant insofar as it gives answers to basic questions about the content of the offender’s portrait, his psychological behavior when committing illegal actions. The criminological characteristics of a person are revealed through an analysis of the structure of a person’s personality itself, thereby creating the basis for the motivational basis of criminal behavior and the effective fight against domestic violence. The theoretical basis of criminology in these issues is of paramount importance in developing sound recommendations for the prevention of domestic violence. This article examines the concept of “criminological characteristics”, “criminological portrait of a criminal in domestic violence”. The fundamental research methods are the method of document analysis and the method of general scientific knowledge. The novelty of this article lies in the proposed conclusions for improving the fight against domestic violence. The value of this study lies in the fundamental ideas developed during the research process, and makes an invaluable contribution to further research into the content of domestic violence in Kazakhstan. The conclusions of the article propose fundamental ideas in solving some problems of preventing domestic violence based on an analysis of the criminological portrait of a domestic aggressor.